The Smuts Government's justification of the emergency regulations and the impact thereof on the Ossewa-Brandwag, 1939 to 1945 - La Grange, Anna (Scientia Militaria - South African Journal of Military Studies, 2020)
The Second World War was a dynamic time in the South African past – a time when war was not only fought against foreign enemies but also at home within the Afrikanerdom. The metaphorical battle on the home front had two sides. The one was resistance against the Smuts government’s war effort, and the second was the Smuts government’s actions to curb internal unrest. The main attempt to dampen the internal unrest manifested itself in the form of various emergency regulations and war measures.  These regulations and measures affected the Ossewa-Brandwag, a dualistic organisation within the Afrikanerdom, which would eventually lead the resistance directly against the war effort. This article delves into the Smuts government’s justification of the emergency regulations and analyses the impact thereof on the Ossewa-Brandwag.